Health Systems in East Asia : What Can Developing Countries Learn from Japan and the Asian Tigers? - Wagstaff, Adam (World Bank, Washington, DC, 2012)
The health systems of Japan and the Asian Tigers--Hong Kong (China), the Republic of Korea, Singapore, and Taiwan (China)--and the recent reforms to them provide many potentially valuable lessons to East Asia's developing countries. All five systems have managed to keep a check on health spending despite their different approaches to financing and delivery. These differences are reflected in the progressivity of health finance, but the precise degree of progressivity of individual sources and the extent to which households are vulnerable to catastrophic health payments depend too on the design features of the system-the height of any ceilings on social insurance contributions, the fraction of health spending covered by the benefit package, the extent to which the poor face reduced copayments, whether there are caps on copayments, and so on. On the delivery side, too, Japan and the Tigers offer some interesting lessons. Singapore's experience with corporatizing public hospitals-rapid cost and price inflation, a race for the best technology, and so on-shows the difficulties of corporatization. Korea's experience with a narrow benefit package shows the danger of providers shifting demand from insured services with regulated prices to uninsured services with unregulated prices. Japan, in its approach to rate-setting for insured services, has managed to combine careful cost control with fine-tuning of profit margins on different types of care. Experiences with diagnosis-related groups in Korea and Taiwan (China) point to cost-savings but also to possible knock-on effects on service volume and total health spending. Korea and Taiwan (China) both offer important lessons for the separation of prescribing and dispensing, including the risks of compensation costs outweighing the cost savings caused by more "rational" prescribing, and cost-savings never being realized because of other concessions to providers, such as allowing them to have onsite pharmacists.